41.0k views
4 votes
Of the following options, what could be a possible first step in solving te equation 3x-1=2x+4?

User Honor
by
5.6k points

2 Answers

3 votes

First you need to combine like terms.

3x+2x= 6x

-1+4=3

SO the answer will be,

6x+3.

User Muhammad Saleh
by
5.2k points
3 votes

Note that in this equation, you are solving for x.

The first step i would take is "isolating the x". To do so, add 1 to both sides, and subtract 2x from both sides

3x (-2x) - 1 (+1) = 2x (-2x) + 4 (+1)

3x - 2x = 4 + 1

x = 5

hope this helps

User Qingbo
by
5.8k points